TEACHING READING COMPREHENSION BY USING PROBING-PROMPTING LEARNING STRATEGY TO THE EIGHTH GRADE STUDENTS OF SMPN 7 PALEMBANG - Sherly Marliasari; Tika Okta (STKIP PGRI Lubuklinggau, 2018)
The objective of the study was to find out whether or not it is effective to teach reading comprehension by using probing-prompting learning strategy. The researcher used pre experimental method. The population of the study was the Eighth Grade Students of SMPN 7 Palembang was 337 students. The researcher took the sample 36 students by using the convenience sample. Analyzing the data was collected through a written test and calculated by SPSS 16. Based on the data analysis, the result of pretest indicated that the highest score was 70 and the lowest score was 50. In the result of t-test, it was founded that t-obtained was 9.574, so it was higher than the critical value of t-table was 1.690 with (df-1) n=35 at the level of significance 0.05 for one-tailed test. It means that the alternative hypothesis (Ha) was accepted.